Anti-microbial investigation of Suaeda baccata (chenopodiaceae) - Al-Mohammadi S. Suhad; Al-Khateeb Ekbal; Al-Shamma Ali (College of Pharmacy / Mustansiriyah University, 2005)
This study includes the detection of the anti microbial activity of both the plant extract of Suaeda baccata (Chenopodiaceae) and its constituent the trigonelline alkaloid, against several microorganisms (Staphylococcus aureus to represent one member of Gram positive bacteria, Escherichia coli to represent one member of Gram negative bacteria and Candida albicans to represent one member of fungi) in that trigonelline alkaloid and the plant extract, showed an antibacterial activity against the growth of gram positive bacteria, Staphylococcus aureus, while gram negative bacteria, Escherichia coli and the yeast, Candida albicans were resistant to both.